Organizational change for school development: a study of implementation of school-based decision-making groups - Dellar, Graham Brendon (Curtin University, 1990)
This study analyses, interprets and describes the dynamics of the change process occurring as members of three secondary school communities attempted to implement a Ministry of Education initiative involving the establishment of a school-based decision-making group.A review of literature on innovation and change, organization theory and school improvement is presented as a basis for the establishment of a conceptual framework for the study. Within this framework, implementation is viewed as the interaction of the innovation with the characteristics of each adopting school. These interactions are viewed as occurring within two change environments. The first, the general change environment, is shared by all schools under study. This environment reflects the broader economic, political and educational pressures prompting change. The second environment is specific to each school. It forms the immediate context within which the implementation process occurs. Before examining the specific nature of the implementation process within each school site, attention is given to the general change environment from which the innovation emerged. This is accompanied by an analysis of the evolutionary nature of the innovation itself as it underwent progressive clarification at Ministry of Education level.To assess the influence that specific environmental characteristics have on the implementation process, schools with markedly differing setting characteristics were selected for study. An instrument to assess school organizational climate was developed, (SOCQ) and then administered to twenty three secondary schools in the Perth metropolitan area. The resulting data were analysed and used to select three schools with distinctly different organizational climate characteristics for closer study of the implementation process.For each school, detailed portrayals of the implementation events were distilled in order to capture the complexities of the change. Cross-case analysis of the casestudy data was then undertaken to draw out particular issues, events and interactions that appeared to be of importance in directing the implementation process within individual schools and across all three sites.The final chapter addresses the initial set of research questions and presents a series of findings and associated recommendations stemming from this study. Of the range of findings to emerge from the study three appear to be of critical importance for our understanding of the organizational change process. The first finding is that the implementation of a policy innovation is best viewed as a process of "interactive modification" That is, a process whereby the innovation prompts modifications to be made to the adopting system and where the adopting system prompts modifications to be made to the innovation in a complex and dynamic manner. This finding goes beyond the notion of of change as "adaptation" or "evolution" to suggest more dynamic and interrelated process of change occurring to both the innovation and the adopting system. The second finding is that adopting system, the school, is best viewed as an open social system influenced by and yet exerting an influence upon the broader change environment in which it exists. Consequently the implementation of change is subject to influence by infomation, issues, events and interventions stemming from internal and external sources. The reality of the organizational change process is therefore far more complex and dynamic than previous theories and models of change suggest. A third and related finding is that secondary schools appear to be comprised of a number of sub-systems. The extent to which these sub-systems are interdependent or linked appears to influence not only the school's initial response to change but also the schools capacity to undertake meaningful and significant implementation of an innovation. This finding has implications for the design of specific change strategies that focus on improving the degree of sub-system linkage within a school. Such change strategies might occur prior to or run concurrently with other strategies concerned with the implementation of specific organizational changes.It is hoped that these findings have value for several audiences. First, they should be of particular importance to Ministry and school personnel presently confronted by organizational change. Second, the findings should not only serve to inform those building change theory, but also those educators who might hold responsibility for the implementation of similar policy innovations.